The Branding of Ancient Olympia - Βικάτος, Δημήτριος-Σπυρίδων (Πανεπιστήμιο Πελοποννήσου, 2022)
The subject of this Master Thesis is City Branding and especially in the case of Ancient Olympia, a tourist place, whose name and history are perfectly associated with one of the most famous Brand Name in the world, that of the Olympic Games. By itself, City Branding is a complex and often difficult concept, because it turns an entire city into a product and services and aims to promote it. Marketing strategies are formulated in such a way that they are applied throughout the city. Special emphasis is given to Branding, to the design and promotion of the brand of the place. But in order to maintain a strong Brand, it must offer services and goods, and satisfy the needs not only of the residents but also of the visitors. In particular, the competent bodies of each place aim at the satisfaction of the tourists and formulate the marketing strategies accordingly. Regarding the structure of the Thesis, in the first chapter is the presentation of the place of Ancient Olympia, its historical background and development as well as its role in the Olympic Games from antiquity until today. The second chapter, through a literature review, analyzes the concept of City Branding and Place Branding and the importance of their application in tourist destinations. It also mentions the way in which Ancient Olympia managed to build a strong Brand and Image in antiquity but also how it was reborn in the 19th century, after centuries of obscurity. The third chapter mentions the research methodology, the questionnaire and its variables. The fourth chapter presents the statistical analysis of the data collected from the residents and visitors of Olympia. In closing, the fifth chapter of this Master Thesis presents the results of the research in combination with their conclusions and proposals regarding the tourism development of Ancient Olympia.
Keywords: Ονομασία προϊόντων - Μάρκετινγκ; Αθλητισμός και τουρισμός; Αρχαία Ολυμπία (Ελλάδα); Ολυμπία (Ελλάδα: Επαρχία); Ολυμπιακοί αγώνες (Αρχαίοι) - Ελλάδα; Branding (Marketing); Sports and tourism; Archaia Olympia ( Greece); Olympia ( Greece: Province); Olympic games (Ancient) - Greece; City Branding; Place Branding; Ancient Olympia; Brand Name